Asian cities: colonial to global - Bracken, Gregory (Asian citites, 2015)
Cover -- Contents -- Acknowledgements -- Introduction -- Asian Cities: Colonial to Global -- Gregory Bracken -- Part One -- Post-colonialism -- 1. Gambling, City, Nation -- Popular Illegality and Nation Building in Singapore, 1960s-1980s -- Kah-Wee Lee -- 2. The Death of the Pasar Malam -- The Counterpoint to Development in the Singapore Story -- Elmo Gonzaga -- 3. Artifice and Authenticity -- Postcolonial Urbanism in Macau -- Thomas Daniell -- 4. Urban Art Images and the Concerns of Mainlandization in Hong Kong -- Minna Valjakka -- Part Two -- Networks -- 5. Honkon Nippō and Hong Kong-Japan Relations -- Re-examining the Geopolitical Position of Colonial Hong Kong in East Asia before the End of World War II -- Wilson Wai Shing Lee -- 6. Chain Reactions -- Japanese Colonialism and Global Cosmopolitanism in East Asia -- Faye Yuan Kleeman -- 7. Old Networks with New Users -- Mapping Global Mobility between Dongguan and Hong Kong -- Max Hirsh -- 8. Asian Cities in the Global Maritime Network since the Late Nineteenth Century -- César Ducruet -- 9. Back to the Future -- Feasible Cost-Sharing Co-operation in the Straits of Malacca -- Senia Febrica -- Part Three -- Cities and Buildings -- 10. Rallying Towards the Nation -- Theatre of Nation Building in Post-colonial Dhaka -- Kishwar Habib and Bruno De Meulder -- 11. Selectively Connected -- New Songdo and the Production of Global Space -- Bridget Martin -- 12. The Vernacular and the Spectacular -- Urban Identity and Architectural Heritage in Southeast Asian Cities -- Rita Padawangi -- 13. Heritage in Times of Rapid Transformation -- A Tale of Two Cities -- Yangon and Hanoi -- William Logan -- 14. Small-scale, Bottom-up -- Cosmopolitan Linkages Reglobalizing Shanghai's City Centre -- Ying Zhou -- Conclusion -- Global Cities in Asia -- Gregory Bracken -- Contributors -- Bibliography -- Index -- Figures.